Absent or neglected forms from Polish schools of supporting teachers in inclusive education - Zenon Gajdzica (Studia z Teorii Wychowania)
Caring for the quality of inclusive education depends on many factors, among which one of the most important is the variety of forms of supporting teachers. The following forms are significant: special needs coordinators (SENCo) in mainstream schools, teachers (assistants) co-organizing the educational process in mainstream classes and institutional partnerships of special and mainstream schools. The aim of the study is to provide a general description of the three aforementioned forms of supporting mainstream teachers in implementing inclusive education. The starting point is the thesis that these solutions are practically absent or hardly ever appear in the Polish practice. Moreover, they belong to the issues which are (with very few exceptions) omitted in scientific and methodological studies published in Polish. As a result, teachers of a particular subject or early childhood education who carry out tasks related to the education of learners with special educational needs are deprived of genuine support in educational practice.